Multiplicadores fiscais em condições de choques de oferta ou demanda: uma análise da economia brasileira entre 1996 e 2016 - Magalhães, Sérgio Lemos de (2017)
The work evaluates the behavior of the Brazilian government spending fiscal multiplier between 1996 and 2116. Through a SVAR model, it was analyzed the behavior of the multiplier given a shock in government spending. In addition to the analysis of the standard model, it was also possible to measure, using dummy variables the impact of: the state of the economy, below and above the natural product, and given the present shock, demand or supply. As presented by the national and international literature, the results reflected better performance in the economy in times of product below its potential and in a situation of demand shock. Although it had more favorable results it still lower than 1, demonstrating low efficacy of the multiplier, in which it was pointed out structural situations of the Brazilian economy such as the high indebtedness and public spending as possible vectors of loss of efficiency. Finally, the study evidenced the behavior of the multiplier in a specific situation of negative supply shock in which we had results higher than 1, indicating that the multiplier should be analyzed in certain circumstances.